Inhibition of Oct 3/4 mitigates the cardiac progenitor-derived myocardial repair in infarcted myocardium. Issue 1 (December 2015) - Zhao, Yu; Du, Jianfeng; Chen, Youfang; Tang, Yaoliang; Qin, Gangjian; Lv, Guorong; Zhuang, Shougang; Zhao, Ting
Abstract Background Recent evidence has demonstrated that cardiac progenitor cells play an essential role in the induction of angiomyogenesis in infarcted myocardium. We and others have shown that engraftment of c-kit+ cardiac stem cells (CSCs) into infarcted hearts led to myocardium regeneration and neovascularization, which was associated with an improvement of ventricular function. The purpose of this study is aimed at investigating the functional role of transcription factor (TF) Oct3/4 in facilitating CSCs to promote myocardium regeneration and preserve cardiac performance in the post-MI heart. Methods c-kit+ CSCs were isolated from adult hearts and re-introduced into the infarcted myocardium in which the mouse MI model was created by permanent ligation of the left anterior descending artery (LAD). The Oct3/4 of CSCs was inhibited by transfection of Oct3/4 siRNA, and transfection of CSCs with control siRNA serves as control groups. Myocardial functions were evaluated by echocardiographic measurement. Histological analysis was employed to assess newly formed cardiogenesis, neovascularization, and cell proliferations. Terminal deoxynucleotidyltransferase (TdT) nick-end labeling (TUNEL) was carried out to assess apoptotic cardiomyocytes. Real time polymerase chain reaction and Western blot were carried out to evaluate the level of Oct 3/4 in CSCs. Results Two weeks after engraftment, CSCs increased ventricular functional recovery as shown by a serial echocardiographic measurement, which is concomitant with the suppression of cardiac hypertrophy and attenuation of myocardial interstitial fibrosis. Suppression of Oct 3/4 of CSCs abrogated functional improvements and mitigated the hypertrophic response and cardiac remodeling. Transplantation of c-kit+ CSCs into MI hearts promoted cardiac regeneration and neovascularization, which were abolished with the knockdown of Oct3/4. Additionally, suppression of Oct3/4 abrogated myocyte proliferation in the CSC-engrafted myocardium. Conclusion Our results indicate that CSCs-derived cardiac regeneration improves the restoration of cardiac function and is mediated through Oct 3/4.